Analysis of Student Errors in Solving Statistics Problems in terms of Mathematical Ability - Nurwati Djam'an; Sahid Sahid; Fitrah Auliyah (SAINSMAT: Journal of Applied Sciences, Mathematics, and Its Education, 2022)
This research is a qualitative research that aims to find out student errors. The research subjects consisted of 3 students. The technique of taking the subject in this study amounted to three students with high, medium and low mathematical ability categories. The instrument in this study used tests and interviews. Data collection techniques in this study are giving tests and interviews. The data analysis technique uses the Miles and Huberman model, namely data reduction, data presentation, and conclusions. Based on the results of the study, it showed that students with low abilities made four types of errors, namely, comprehension errors, transformation errors, process skill errors. Students with moderate math skills make three types of errors, namely, transformation errors, process skill errors, and encoding errors, and students with high math skills make 2 types of errors, namely transformation errors and encoding errors.